Reliability and validity analysis of the Quality of Life, Satisfaction and Pleasure Questionnaire (Q-LES-Q) in Public Health workers - Hauser, María Paz; Garcia, Horacio Daniel; Leporatti, Jorge (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
The quality of Life Questionnaire: satisfaction and Pleasure (Q-LES-Q) (Endicott, Harrison y Blumenthal, 1993; WHOQOL Group, 1995), widely used and recognized by the scientific community, it has not been reviewed in population in Argentina. For this reason, this study was oriented to determine the reliability and validity of seven subscales. We worked with a probabilistic sample of 497 public health workers (M=38 years; SD=9,48). The results indicated adequate internal consistency indexes; by means of the analysis of principal components some subscales with multifactorial structure were detected, while others retained their original structure. By means of rotation Oblimin was obtained a distribution of items consistent with the theoretical constructs, so it was concluded that their use in this population would be pertinent.